Trust, distrust and control : an inductive, field study of a Singapore-Chinese joint venture. - Tan, Derek Weixiang. (2008)
This report aims to examine the relationship of trust, distrust and controls through an inductive field study of a Singapore SME managing its Joint Venture (JV) in China. Specifically, we were intrigued by the coexistence of high trust and low distrust between foreign and local JV Partners even at the formation stage of the venture.